A study to assess the effectiveness of information booklet on knowledge of mothers regarding prevention of home accidents among children under five years in selected areas of urban community - Rajesh Salvi, Jayashree (International Journal of Nursing Research, 2023)
Accidents are epidemic in the developed countries. In India accidental deaths are also in increase, accidents come after malnutrition, respiratory, gastrointestinal diseases, leukaemia or meningitis. “Home accidents are a substantial health problem for young children. An accident is a sudden cause of death or an emergency in children” Accidents are usually related to the growth and development of the children. Aim: To find out the association between mothers knowledge regarding prevention of home accidents among children (0-5 years) before and after giving information booklet. Methods: Fifty samples were selected using non probability purposive sampling and given Pre test & Post Test. The samples included are from mothers of 0-5 years old children in slum chawls of khar in Urban Mumbai. Fifty samples were selected using non probability purposive sampling. A self administer questionnaire was prepared to find the association between knowledge regarding prevention of home Accidents in mothers. It was established by experts in the field and reliability was tested using Split half method and Cronbachs Alpha. Results: The„t‟ value was calculated for comparison of pretest and post test score of information booklet. There was significant difference in pretest- post test mean score, which showed that the information booklet was effective. The t value was also calculated with independent t test, paired t test, chi square test and kolmogrov smirnov test. There was significant difference in pre-test- post test mean score, which showed that the information booklet was effective. Conclusion: Association of knowledge with demographic variables using ANOVA showed significant as well as non significant results.